Initial evaluation to the performance of the Iraqi actors playing The role of ( Mackbeth ): مظـفر كاظم محـمد (Al-Academy, 2016)
From 1979 to 1999 several theatricl groups had produced (Mackbeth) by shakespear which were directed by different director and the role being played by different actors. So the questions are: How did those a Iraqi actors approach that character by their performance? Did they interpret the character Truelly as the poet wanted to be. The researcher aims to find out the true performance by the actor who impersonate (mackbeth) as a wicked personality, who had un rational ambition. The researcher also aims to expose the style of acting fallowed by the Iraqi actors in that play. In chapter of review of literature, The researcher discusses the weaning and procedure of the actor performance which include characterization and transformation. He also discusses the three dimention of any charater in the theatre – the physical, the social, and the by chological. Chapter two includes analysis of (Mackbeth) personality according to the perspective. In chapter three of this research the researcher analyzes the sample including three production of (Mackbeth), the first was directed by Mursil ALzaidy, the second was directed by Shafik Mehdy, the third was directed by Sallah AL-Kassab. All those directors are instructors at the Department of theatre Ail- College of Fine Art, university of Baghdad. The researcher Concludes that only the first actor (Kamiran Rauof) approached the vole of (Mackbeth) quite well and had given the other two were far from the true perspective because they had not taken the three dimensions of the character in mind